2015
DOI: 10.1002/pc.23873
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of PMMA grafted calcium carbonate whiskers and its reinforcement effect in PVC

Abstract: In this study, calcium carbonate (CaCO3) whiskers were grafted with poly(methyl methacrylate) (PMMA) by in situ emulsion polymerization using γ‐methacryloxy propyl trimethoxyl silane (γ‐MPS) as a coupling agent, and the properties of resultant whisker were determined using Fourier transform infrared (FTIR) spectroscopy, energy dispersive spectroscopy (EDS), X‐ray photoelectron spectroscopy (XPS), and thermogravimetric analysis (TGA). The results show that PMMA has been successfully grafted onto the surface of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…[31][32][33] Recently, Yuan and Cui et al found that CSWs coated by crosslinked polyvinyl alcohol (PVA) or chitosan (CS) greatly improved the tensile and impact properties of CSW/PVC composites, which could be attributed to the good affinity between PVC and PVA or CS molecules coated on the surface of CSWs. 17,23,[34][35][36] Coupling agents are usually used to modify the inorganic llers to improve their interfacial strength with polymers, 37,38 and the most commonly used coupling agents for this purpose include silane coupling agents, 39,40 titanate coupling agents 41,42 and fatty acids. 43 Monte and Sugerman…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] Recently, Yuan and Cui et al found that CSWs coated by crosslinked polyvinyl alcohol (PVA) or chitosan (CS) greatly improved the tensile and impact properties of CSW/PVC composites, which could be attributed to the good affinity between PVC and PVA or CS molecules coated on the surface of CSWs. 17,23,[34][35][36] Coupling agents are usually used to modify the inorganic llers to improve their interfacial strength with polymers, 37,38 and the most commonly used coupling agents for this purpose include silane coupling agents, 39,40 titanate coupling agents 41,42 and fatty acids. 43 Monte and Sugerman…”
Section: Introductionmentioning
confidence: 99%
“…PVC composites were prepared as described previously. [6][7][8][9] Briefly, PVC resin (100 phr) was combined with a certain amount of FA or modified FA (denoted as mFA) using organotin (2 phr) as a heat stabilizer and DOP (6 phr) as a plasticizer. After that, the mixture was stirred with GMS (0.6 phr), ACR (4 phr), and liquid paraffin (0.4 phr), and then transferred to a two-roll mill at 170 C for 10 minutes.…”
Section: Synthesis Of Pvc Compositesmentioning
confidence: 99%
“…[4] The addition of inorganic fillers such as SiO 2 , CaSO 4 , CaCO 3 , and C-based fillers (eg, carbon black, carbon nanotubes, and graphene oxide) is an effective method for improving the overall properties of PVC. [5][6][7][8][9][10] Fly ash (FA) is a reinforcing filler that can dramatically improve the impact and thermal resistance, as well as the modulus of PVC, owing to its beneficial characteristics such as heat resistance, excellent mechanical strength, resistance to chemical corrosion, low price, abundance and more importantly, ease of industrialization. [10][11][12][13] FA is the main solid waste discharged from the combustion of pulverized coal in thermal power plants, and it is now the largest single source of industrial solid waste.…”
Section: Introductionmentioning
confidence: 99%
“…Interfacial interactions between matrix and filler are critical to the performance of polymer-based composites [10,11] . It is clear that a good interfacial adhesion allows an efficient stress transfer between matrix and fillers, which is helpful for the composites to absorb more energy and improve its mechanical properties [12] .…”
Section: Introductionmentioning
confidence: 99%